Designing whole-systems commissioning: Lessons from the English experience. (July 2012) - Williams, Iestyn; Bovaird, Tony; Brown, Hilary; Allen, Kerry; Dickinson, Helen; Kennedy, Jane; Glasby, Jon
Abstract : The primary aims of this study were to identify determinants of successful strategic commissioning and to assess the overall state of current knowledge. It involved a review of the published literature and interviews with those involved in strategic commissioning in England. The combined evidence from these two sources suggests that structural solutions alone cannot deliver effective relationships and will not be effective when relationships are neglected. There is a prior requirement for staff, partner, and political buy-in. Work is required to ensure the right balance and distribution of commissioning skills and competencies. It is important to note here that many of the skills needed for strategic commissioning may be found in partner agencies (including providers), so organizational boundaries must be seen as porous as the new commissioning/provider roles emerge and are refined. Finance and incentive alignment are also crucial to ongoing strategic commissioning since organizations that contribute to the achievement of multiple outcomes will expect funding streams to recognize and reward these achievements. Overall, while evidence and evaluation are important, in a rapidly changing environment there are no clear-cut guidelines for success and there is an equal need for experimentation and flexibility.